PENINGKATAN DAYA SAING KEDELAI LOKAL TERHADAP KEDELAI IMPOR SEBAGAI BAHAN BAKU TEMPE MELALUI PEMETAAN FISIKO-KIMIA - Kukuk Yudiono (Agroindustrial Technology, University of Trunojoyo Madura, 2020)
The main problem encountered in the production of tempeh was its raw material, namely soybeans dominated by soybean supplied from other countries, mainly dominated by imported products from the United States. The majority of tempeh craftsmen's perception is that imported soybeans are superior to local soybeans. This is of course unfortunate because it will further aggravate the competitiveness of local soybeans. This research was conducted to explore the advantages of local soybeans, especially from the physico-chemical aspects of imported soybeans. The research objective was to map the physico-chemical properties of local and imported soybeans as raw material for tempeh. One factor trial design was used, with soybean varieties (4 local and 1 imported) as a factor. Variables observed included: antioxidant, bulk density, swelling power, plant quality, seed size, WAI, WSI, protein, yield, and density. The results obtained: 1) antioxidant : Devon 1 imported soybeans, 2) bulk density: fourth of local soybeans = imported soybeans, 3) swelling power : Argomulyo = imported soybeans, 4) quality of cooking: fourth of local soybeans imported soybeans, 5) seed size : Grobogan and Argomulyo imports, 6) WAI: Argomulyo and Demas imported soybeans, 7) WSI: Devon = imported soybeans, 8) protein: Grobogan and Detam imported soybeans, 9) density: Bromo imported soybeans, 10) extraction value: Anjasmoro, Argomulyo, and Grobogan imported soybeans.